Salivary Streptococcus mutans and dental caries in relation to nutritional status among 6 years old children (Mustansiria Dental Journal, 2018)
Background: Nutritional status is the mirror image of health and one of its mostaccurate indicators. Normal salivary gland functions are essential for maintenanceof oral health. Salivary flow rate and composition which could be influenced bynutritional status. The aim of this study was to investigate the effect of nutritionalstatus on Streptococcus mutans and their relations to dental caries.Materials and methods: Stimulated saliva was collected from 28 children with anage 6 years old. Those randomly selected children were divided into wellnourishedand chronic malnourished children according to their age, weight andheight indicators. Dental caries examination of primary teeth was assayedfollowing the criteria of WHO. Microbiological assessment of Streptococcusmutans was done after measuring the salivary flow rate.Results: No significant differences were found between well-nourished and chronicmalnourished children in caries experience. Chronic malnourished children had asignificant lower salivary flow rate and higher mean counts of salivaryStreptococcus mutans than that of well-nourished children. Significantcorrelations were found between nutritional status with flow rate andStreptococcus mutans.Conclusion: Early identification of malnourished children will lower the prevalenceof dental caries and enhance their quality of life.